Sophoridine inhibits proliferation and migration by targeting PIM1 in breast cancer - Lu Chen; Yuting Xia; Liangliang Min; Yuqin Zhang; Da Huang; Yulu Zhang; Aihua You; Zhihua Li (Pharmaceutical Biology, 2025)
Context Sophoridine, an alkaloid quinolizidine derived from Sophora flavescens Aiton (Fabaceae), has strong anti-tumor activity in a variety of malignancies. Nevertheless, the effects and underlying mechanism of sophoridine on breast cancer are not fully understood.Objective To identify the key targets and potential pharmacological mechanisms of sophoridine against breast cancer.Materials and methods MCF-10A, MCF-7 and MDA-MB-231 cells were treated with sophoridine for 24 or 48 h. MTT, colony formation assay, flow cytometry, wound healing, and Transwell assay were employed to illustrate the anti-tumor effects of sophoridine on breast cancer. Network pharmacology and molecular docking were used to determine the targets for sophoridine in breast cancer, and confirmed by molecular dynamics simulation and CETSA-western blot assay. Additionally, the functional rescue and signaling pathway regulated by sophoridine was analyzed.Results Sophoridine suppressed the proliferation, migration, and invasion of breast cancer cells. The IC50 value of sophoridine for 48 h in MCF-10A, MCF-7 and MDA-MB-231 was 363 μM, 87.96 μM and 81.07 μM, respectively. PIM1 was the key target for sophoridine in breast cancer. Furthermore, PIM1 overexpression significantly reversed the suppressive impacts of sophoridine on growth and migration in breast cancer cells. Mechanistically, sophoridine inhibited the phosphorylation of ASK1 and activated JNK/p38 MAPK signaling pathway by downregulating PIM1 expression, and thus exhibited anti-tumor effects.Discussion and Conclusion Taken together, sophoridine relies on targeting PIM1 to inhibit cell proliferation and migration in breast cancer, which might be related to the activation of ASK1/MAPK axis, suggesting the therapeutic potential of sophoridine for breast cancer.